Analysis of the Experience-Based Design Feedback Data on a National Scale. (December 2020) - Rahman, Sakib; Thompson, Deborah; Clayton, Alice; Conroy, Simon; Tite, Matt
The United Kingdom Office of National Statistics population estimates that 10 million people are aged 65 years and older, of which some would be considered frail. This is conceptualized as a complex progressive loss of physiological and social function. In order to establish and evaluate appropriate services, feedback tools designed for this patient group have begun to take greater importance, which the Acute Frailty Network has been developing using experience-based design. These tools focus on the experience of frail patients in the settings of accident and emergency and the acute medical unit. An analysis of data from 12 hospitals was used to look at the common emotions and comments expressed at the key touchpoints. A total of 609 respondents were used in the analysis, revealing that patients expressed mostly positive experiences. The areas with the most negative emotions and comments were in the domains "being admitted, " "first assessment, " and "preparing to leave hospital." We would recommend that future quality improvement projects focus in improving the communication standards around the admission and discharge process.